The inhibitory effect of some pyrazole ligands and their Cu(II) complexes on the growth of Escherichia coli, Klebsiella-Enterobacter spp., and Staphylococcus aureus - Majda Šahman Zaimović; Milica Kosović Perutović; Gordana Jelušić; Ana Radović; Željko Jaćimović (Frontiers Media S.A., 2022)
The aim of this study was to evaluate the inhibitory activity of chemistry products against the growth of Escherichia coli, Klebsiella-Enterobacter spp., and Staphylococcus aureus. Pyrazole derivatives (4-bromo-2-(1H-pyrazol-3-yl)phenol, 4-nitro-3-pyrazolecarboxylic acid, N-(benzyloxycarbonyl)-1H-pyrazole-1-carboxamidine), 3-amino-5-hydroxypyrazole, 3,5-pyrazoledicarboxylic acid monohydrate, and selected complexes of Cu(II) with the mentioned pyrazoles as ligands were used as chemistry bioactives for antibacterial activity. The testing method was carried out according to the disc diffusion method. Some compounds have shown inhibitory effects against the growth of E. coli. A small number of compounds have shown inhibitory effects against the growth of Klebsiella-Enterobacter spp. but did not show inhibitory effects on Staphylococcus aureus compared to amoxicillin as a standard.